Rights and freedoms in old age: explicit paternalisms and implied old ages of the pandemic - Dabove, María Isolina (2020)
Purpose: This research paper aims to analyze an emblematic sentence regarding the rights and freedoms of the elderly in the context of the emergency caused by COVID-19 (Lanzieri, S. c / GCBA s / amparo - others, 04/20/2020). Introduction: The studied case questioned a regulation settled by Buenos Aires City, which obliged people aged 70 years and over to request special permission from the local authority to carry out activities considered essential for everyone. The main argument was the generic categorization of the elderly as a population at risk, but that regulation restricted their right to exercise freedoms on equal terms as others. Development: From a trialist perspective of Elder Law, this paper analyzes the facts, rules and judicial criteria prevailing at the time of the verdict during the pandemic. Conclusions: According to the investigation approach, the sentence shows the discriminatory nature of the objected regulation, its unnecessary paternalistic edges, the unlawful interference, and overprotection of the elderly, whose consequences reinforced ageism and disempower older persons